2020
DOI: 10.1101/2020.03.23.003350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibiotic resistance genes and class 1 integron: Evidence of fecal pollution as a major driver for their abundance in water and sediments impacted by metal contamination and wastewater in the Andean region of Bolivia

Abstract: 26Water and sediment samples affected by mining activities were collected from 27 three lakes in Bolivia, the pristine Andean lake Pata Khota, the Milluni Chico lake 28 directly impacted by acid mine drainage, and the Uru-Uru lake located close to 29 Oruro city and highly polluted by mining activities and human wastewater 30 discharges. Physicochemical parameters, including metal compositions, were 31 analyzed in water and sediment samples. Antibiotic resistance genes (ARGs), 32 were screened for, and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The enzyme was also prevalent in water from coastal areas and was associated with a variety of host bacteria [78]. Additionally, it was found in higher absolute abundance in effluent WWTPs water compared to upstream locations or downstream locations [53,54,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79], which aligned well with the current results. In this regard, the comparison of acquired resistance and co-occurrence of ARGs and MGEs identified more hits in the first location, Dragushinovo, that is immediately after the WWTP, thus being consistent with the results of other studies [66][67][68][69][70][71][72][73].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The enzyme was also prevalent in water from coastal areas and was associated with a variety of host bacteria [78]. Additionally, it was found in higher absolute abundance in effluent WWTPs water compared to upstream locations or downstream locations [53,54,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79], which aligned well with the current results. In this regard, the comparison of acquired resistance and co-occurrence of ARGs and MGEs identified more hits in the first location, Dragushinovo, that is immediately after the WWTP, thus being consistent with the results of other studies [66][67][68][69][70][71][72][73].…”
Section: Discussionsupporting
confidence: 89%
“…The full potential of high-throughput sequencing data is often not realized, as many studies focus on a limited subset of analyses, such as the detection and analysis of ARGs. While ARG profiling and detection of anthropogenic factors such as intl1 [52][53][54] and ARGs of clinical relevance such as carbapenem hydrolysing variants of OXA, KPC, and NDM is essential for understanding the spread of AMR, they represent only a fraction of the information that can be derived from sequencing data. Our study extended beyond that by integrating metagenome-assembled genomes (MAGs) into our interpretation of the ARGs, by revealing their antimicrobial resistance genetic potential, thus complementing ARG discovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Agramont et al investigated the contamination of ARGs and class 1 integrons in water and sediment samples that were impacted by human wastewater and mining activities. The authors found that fecal pollution was likely a major driver of ARG and intI1 genes in comparison to the heavy metal pollution [66]; however, it was still unclear if there were any synergistic effects from both fecal pollution and heavy metals on the overall levels and spreads of ARGs and integron genes in the considered aquatic environments.…”
Section: The Abundance Of Arg Genes In the Saigon River Impacted By Anthropogenic Activitiesmentioning
confidence: 99%
“…There are reports of contamination with traces of mainly β-lactams and aminoglycosides in environmental and food sources [82, 83]. Human and animal faecal contamination of ground and surface water sources has allowed the spread of pathogenic micro-organisms, antibiotics and other contaminants, increasing the abundance of antibiotic resistance genes associated with class 1 integrons in aquatic environments [83, 84].…”
Section: Discussionmentioning
confidence: 99%